Perlindungan Anak dalam Keluarga Poligami Menurut Hukum Islam - Islamiyah, Nani Nadia (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2023)
According to article 1 UU No. 1 of 1974, "Marriage" refers to the marriage and bonding of a man and a woman as a close friend with the aim of creating a family (a tangga house) that is virtuous and well-adjusted based on the principles of the Yang Maha Esa. However, in the current state of affairs, the monogamous marriage organization is prohibited by Pasal 3 UU No. 1 of 1974 from being used by relatives or friends, and polygamous also occurs as a result of a disagreement with the sister organization, while the brother organization is reluctant to use the sister organization due to various reasons. On the side, polygamous frequently results in unfavorable effects on the safety of children in polygamous groups if there are many unruly members. For this reason, it is necessary to discuss the implementation of the law's protection of children, factors that contribute to child abuse, and the measures taken to prevent child abuse within the polygamous family.This research discusses child protection in the context of polygamous families according to Islamic law. Through an Islamic legal approach, this research identifies the legal and social protection mechanisms implemented to ensure the welfare of children in polygamous family situations. Analysis of Islamic legal principles and their relevance in this context is a focus for understanding how policies and practices can be aligned to protect the rights and interests of children in complex family environments.